Забезпечення розвитку експорту високотехнологічних товарів в умовах зміни векторів зовнішньої торгівлі - Квач, Я. П.; Коваль, В. В.; Циналєвська, І. А. (Видавництво Львівської політехніки, 2015)
Розглянуто проблему забезпечення розвитку експортної діяльності, перш за все, високотехнологічних товарів, в умовах зміни векторів зовнішньої торгівлі. В межах дослідження проаналізовано структуру експорту України для визначення ступеня технологічності основних товарних позицій експорту. Проаналізовано також зарубіжний досвід застосування інструментів підтримки та стимулювання експортної діяльності. В умовах необхідності переорієнтації зовнішніх торговельних зв’язків вітчизняних товаровиробників наведено практичні рекомендації щодо підтримки експортної діяльності національних виробників високотехнологічної продукції. The article examines the problem of the development of exports in the context of changing direction of foreign trade in particular a special attention was paid to support's mechanisms of high-tech product's exports.. Indicators of Ukraine's foreign trade dynamics demonstrate a low effectiveness of the state export policy. The analysis of the commodity structure of Ukraine's exports indicates the raw material orientation of national economy in the system of international division of trade flows. The high-tech products export's value denotes a current low level of technological effectiveness of industrial production. The problem of inefficient export's structure is actualized by the fact that opportunities for manufacturing high-tech products in Ukraine are available, but at present, because of a number of reasons, not implemented. The crisis of modern foreign policy stipulates an acute fluctuations in the foreign trade especially in export of those commodity positions, which belonged to high-tech category, which include such commodity groups as “Aircraft and spacecraft”, “Computer and office equipment” “Electronics communications”, “Pharmaceutical products”, “Scientific instruments”, “ Electrical machinery equipment and their parts “, “Chemicals”, “Non-electrical machinery” and “Arms”. Closing the Russian market for such commodity groups as nonelectrical equipment and aerospace equipment, for which the Russian direction of export reached about 60% of the total, put the production of innovative goods on the brink of survival. Under these conditions the need for sales markets’ reorientation is a prerequisite the preservation and development of national innovation system, given the fact that the production of high-tech products for the domestic market remains unclaimed. Therefore, efforts for diversification of geography of deliveries of Ukrainian high-tech industrial commodities put on the agenda an application of development tools for export activity support in the development and implementation of effective mechanisms for supporting of national exporters when entering foreign markets. The experience of many developed countries, which have succeeded in raising of finished products export, demonstrates a crucial role in these achievements of effective system of state exports support. A cornerstone of the export support system is a mechanism of the financial support; the main instruments are mainly related to improving the efficiency of national export's credit system that is achieved through the strengthening of specialized financial institutions – Export Credit Agency (ECA). Due to the financial support of ECA national companies have the opportunity to receive state-warranty insurance and credit support as well as bank loans for longer periods and more favourable terms. In Ukraine, because of the lack state policy concerning development of infrastructural environment of export activity precisely in terms of the application of instruments of the financial sector, access to domestic exporters to credit funds is extremely difficult. This applies both a provision of investment resources for the modernization of the fixed assets and short-term lending to cover working capital needs. In our opinion, the development of export insurance and crediting via creation of such institutions as national export credit agency is able to provide a way out of crisis of foreign trade for Ukraine since the problem of access to foreign markets, primarily concerning shortage of working capital available for businesses and, at least, lack of investment resources to purchase new equipment and intangible assets. The validity of such a proposal supported by the fact that the creation of such an organization is not against the rules of the World Trade Organization and allowing largely to protect the financial position of domestic producers.
Provision of high-tech goods export in the context of changing foreign trade vectors
Keywords: експорт; високотехнологічні товари; інструменти розвитку експортної діяльності; зовнішня торгівля; export high-tech products; development tools export business; foreign trade